Molecular and morphological markers of neuronal death in acute cerebrovascular accidents - V. A. Kudryavtseva; E. A. Kuzmin; A. V. Moiseeva; M. S. Obelchakova; P. A. Sinitsina; T. I. Filistovich; N. L. Kartashkina; G. A. Piavchenko; A. M. Golubev; S. L. Kuznetsov (Сеченовский вестник)
Acute cerebral circulation disorder is one of the most discussed issues in modern intensive care and neurology, as it is a severe condition, leading to disability or death of the patient, in the absence of immediate medical care. This review discusses general and specific biological markers of stroke, genetic markers of stroke, and current data on their diagnostic significance. The main mechanisms of brain tissue cell death in stroke, such as apoptosis, necrosis, ferroptosis, parthanatosis, sarmoptosis, autolysis, autophagy, oncosis, excitotoxic death are analyzed; the morphological features of the observed processes and their structural manifestations are reviewed. For each type of cell death in nervous tissue, the most frequently detected molecular markers are discussed: specific kinases, Toll-like receptors in the case of apoptosis; serine-threonine protein kinases, components of the polyubiquitin system detected in necrosis; transferrin 1 receptors, typical for ferroptosis; poly(ADP-ribose)-polymerase, whose activity increases in parthanatosis; slow Wallerian degeneration protein that accumulates during sarmoptosis; and other biomarkers characteristic of both individual types of nerve cell death and general pathological processes affecting the brain.